2014
DOI: 10.1111/jftr.12042
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Naturally Occurring Declines in the Antisocial Behavior of Children and Adolescents: A Process Model

Abstract: This review examines why, without clinical intervention, antisocial behavior tends toAntisocial behavior is disordered conduct that creates serious problems for individuals, families, schools, and society. It is associated with violence, drug abuse, academic failure, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
(203 reference statements)
0
8
0
Order By: Relevance
“…It is the way to devote more time and support to teacher professional development. On the other hand, Buck & Dix (2014) asserted that parenting predicts the naturally occurring declines in antisocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is the way to devote more time and support to teacher professional development. On the other hand, Buck & Dix (2014) asserted that parenting predicts the naturally occurring declines in antisocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews during the past decade highlighted the importance of regulatory strengths in families (Buck & Dix, ; Deater‐Deckard, ; Fishbane, ; Kawabata et al, ; MacPhee, Lunkenheimer, & Riggs, ; Slezackova & Sobotkova, ; Walsh, ). Regulatory strengths include family members' adaptive self‐regulation (cognitive, behavioral, physiological, emotional), interactions between family members that facilitate relationship repair, and family systems' flexible and adaptive responses to internal and external changes and stressors (Fishbane, ; MacPhee et al, ).…”
Section: Strengths In Familiesmentioning
confidence: 99%
“…Dishion & Patterson, 1999). For example, longitudinal research on parent–child interaction has identified key dynamics in the interaction between parents and their children that predict growth in antisocial behavior over time (Buck & Dix, 2014; Hoeve et al, 2009; Rothbaum & Weisz, 1994). These insights may inform the identification of program elements that are likely to affect parenting intervention efficacy.…”
Section: An Iterative Model For Improving Parenting Intervention Effi...mentioning
confidence: 99%